2003
DOI: 10.1029/2002jd002152
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of water complexes in the determination of peroxy radical ambient concentrations: Implications for the atmosphere

Abstract: [1] The objective of this study has been to investigate the origin of the water vapor effect on the chain length (CL) of peroxy radical chemical amplifiers (PERCA). Results of the investigation of the water interference in the determination of peroxy radicals by using the PERCA technique are presented. The experimental conditions have been analyzed and modeled. A nonlinear dependence of the CL on the relative humidity (RH) has been accurately determined. The combined analysis of experimental and simulated resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Unpublished measurements made at the Max Planck Institute for Chemistry in Mainz (Thomas Klüpfel, personal communication) using a Teflon inlet showed a nearly identical response of the chemical amplification factor with respect to water to that observed by Mihele and Hastie (2000). Investigations using a different experimental technique and with an inlet made from plexiglass by Reichert (2000) (see also Reichert et al, 2003) found a much greater sensitivity to water vapour. The interpretation of the various studies is complicated by the fact that Reichert used a different material for the inlet, and a different experimental technique to measure the water effect.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Unpublished measurements made at the Max Planck Institute for Chemistry in Mainz (Thomas Klüpfel, personal communication) using a Teflon inlet showed a nearly identical response of the chemical amplification factor with respect to water to that observed by Mihele and Hastie (2000). Investigations using a different experimental technique and with an inlet made from plexiglass by Reichert (2000) (see also Reichert et al, 2003) found a much greater sensitivity to water vapour. The interpretation of the various studies is complicated by the fact that Reichert used a different material for the inlet, and a different experimental technique to measure the water effect.…”
Section: Methodsmentioning
confidence: 89%
“…The interpretation of the various studies is complicated by the fact that Reichert used a different material for the inlet, and a different experimental technique to measure the water effect. Reichert et al (2003) suggest that the water effect is not solely due to wall loss but is due to reactions involving water complexes and CO or NO. They use a model to reproduce both the measurements of Reichert et al and of Mihele and Hastie (1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration source of a Chemical Ionization Mass Spectrometer (CIMS, Slusher et al, 2004) In fact, the chain lengths determined by the two procedures differed by less than 10%, a difference that is well within the range of the estimated measurement error of the PERCA. Previous work has shown the PERCA chain length to be dependent on both ambient humidity and temperature (Salisbury et al, 2002;Reichert et al, 2003). Therefore, it is usually determined in dry air and then corrected using a calibration factor.…”
Section: Percamentioning
confidence: 99%
“…Switching the two inlets between phases on a minute time scale leads to a continuous amplification and termination signal. Mihele et al (1998Mihele et al ( , 1999 have shown that the chain length of a chemical amplifier is reduced in the presence of atmo-spheric water vapour (see also Reichert et al, 2003). Salisbury et al (2002) demonstrated that the chain length of the Leicester-UEA PERCA instrument falls approximately linearly with increasing specific humidity.…”
Section: Peroxy Radical Measurements (Perca)mentioning
confidence: 99%